THE LONG-TERM PERFORMANCE OF INITIAL PUBLIC OFFERINGS of A-SHARE in SHANGHAI STOCK EXCHANGE DURING 2009-2012 - WEN, SHI (2016)
The long-run underperformance of IPOs is a global phenomenon. It is worth investigating the long-run performance in China’s stock market since stock market in China is quite different from that in developed market. This paper researches the long-run performance of 94 IPOs in Shanghai Stock Exchange during the period of 2009-2012. However, there is no phenomenon of IPOs long-run underperformance based on the 94 IPOs and their average three year buy-and-hold abnormal returns (BHARs) is 12.25% higher than the Shanghai Securities Composite, which is different from the findings of Ritter (1991), Levis (1993) and Khurshed et al (1999). Futhermore, the study attempts to find out the variables in explanatory theories that influence the IPOs long-run performance. Due to the outperformance phenomenon, investors are suggested to invest in IPOs in long term, such as three years, rather than in short term (e.g. one year) when stock market is steady. In addition, it is better to choose the IPOs with the following characteristics: lower market adjusted initial returns, lower price earnings ratio, lower gross proceeds, and lower average return on equity for the last 2 year before IPOs and higher annual revenue. In addition, stocks of companies belonging to Industrials are not a good choice to buy and hold.